2010
DOI: 10.1016/j.sdentj.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The elastomers for complete denture impression: A review of the literature

Abstract: This article reviews the current trends in materials used for complete denture impression. Peer-reviewed articles, published in English and in French between 1954 and 2007, were identified through a MEDLINE search (Pubmed and Elsevier) and a hand search of relevant textbooks and annual publications. Emphasis was made on the characteristics of the elastomers, their manipulation, the different techniques used, and the quality of the impression obtained. The combination of excellent physical properties, handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 75 publications
0
18
0
4
Order By: Relevance
“…Constata-se que a utilização de novos materiais elastoméricos nos últimos dez anos têm aumentado, substituindo os materiais antes preferidos 18 . Os silicones por adição apresentam melhor estabilidade dimensional, pois não gera subprodutos após a polimerização 19 .…”
Section: Materiais De Moldagemunclassified
See 1 more Smart Citation
“…Constata-se que a utilização de novos materiais elastoméricos nos últimos dez anos têm aumentado, substituindo os materiais antes preferidos 18 . Os silicones por adição apresentam melhor estabilidade dimensional, pois não gera subprodutos após a polimerização 19 .…”
Section: Materiais De Moldagemunclassified
“…Quando acionado o gatilho, o êmbolo presente é impulsionado de encontro às pastas permitindo a mistura e obtendo uma massa uniforme e consistente15 .O polissulfeto (mercaptana) tem como vantagens uma boa estabilidade dimensional e precisão, fluidez satisfatória, tempo de trabalho longo, tem baixo custo, é hidrofóbico, é flexível, porém rígido o suficiente para moldagens de áreas retentivas. Como desvantagens, existe o fato de ser restrito aos tecidos moles, a necessidade de ser vazado imediatamente, ter odor desagradável, devido ao tracionamento tem tendência à distorção15,18 . É fornecido em forma de duas pastas, constituinte de um polissulfeto de borracha e um ativador químico que contém peróxido de chumbo15,18 .O poliéter é um material enrijecido, tem menor resistência ao rasgamento e menor deformação, é hidrofílico e proporciona vários vazamentos.…”
unclassified
“…[17] There are certain differences in the hydrophilic behavior of these materials. [18] Sharry [19] recommended that final impression of the edentulous maxilla should be made with ZOE. Taylor et al [20] also found that the alginate hydrocolloid impression material could be used as a final impression material.…”
Section: Journal Of Adhesion Science and Technology 1103mentioning
confidence: 99%
“…Due to the fact that oral mucosal tissues contain major and minor salivary glands, hydrophilic impression materials are being in closer contact with wet mucosa according to hydrophobic ones. [18,23] It is thought that the stronger adhesive force may be resulted from hydrophilic and rigid characteristics of ZOE.…”
Section: Journal Of Adhesion Science and Technology 1103mentioning
confidence: 99%
“…There are four groups of impression materials that are in use for final impression in fixed prosthodontics: polysulfides, polyethers, condensation and addition silicones. Each group of material has its advantages and disadvantages [2]. Elastomers are a group of elastic impression materials.…”
Section: Introductionmentioning
confidence: 99%